2021
DOI: 10.1155/2021/8829860
|View full text |Cite
|
Sign up to set email alerts
|

Study on Seroprevalence and Associated Factors of Bovine Brucellosis in Selected Districts of Afar National Regional State, Afar, Ethiopia

Abstract: Bovine brucellosis is among the top five diseases primarily threatening both public health and livestock economy. Available data are limited to central and highland areas of the country leaving documented literature on the disease in cattle to be found hardly in pastoral and agropastoral regions of the country. As a result, the magnitude and extent of the disease remained to be investigated. A cross-sectional study design was conducted on local Afar cattle aged six months and above from February 2017 to Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In comparison with this finding, the relatively lower seroprevalence of 1.7%, 0.2%, and 1.04% were reported by Tschopp et al [ 60 ] in Arsi zone, Bashitu et al [ 19 ] in Debrebirhan and Ambo Towns, and Tadesse et al [ 61 ] in Becho District, South West Shewa, respectively. However, higher seroprevalence reports were made by Megersa et al [ 62 ] (10.6%) in Borena zone and Negash and Dubie [ 63 ] (5.7%) in Afar region. Similarly, relatively higher results of seroprevalence were reported in other African countries; Matope et al [ 64 ] with 5.6% in Zimbabwe, Mensah et al [ 65 ] with 21.9% in Ghana, and Mai et al [ 66 ] with 24.0% in Nigeria.…”
Section: Discussionmentioning
confidence: 93%
“…In comparison with this finding, the relatively lower seroprevalence of 1.7%, 0.2%, and 1.04% were reported by Tschopp et al [ 60 ] in Arsi zone, Bashitu et al [ 19 ] in Debrebirhan and Ambo Towns, and Tadesse et al [ 61 ] in Becho District, South West Shewa, respectively. However, higher seroprevalence reports were made by Megersa et al [ 62 ] (10.6%) in Borena zone and Negash and Dubie [ 63 ] (5.7%) in Afar region. Similarly, relatively higher results of seroprevalence were reported in other African countries; Matope et al [ 64 ] with 5.6% in Zimbabwe, Mensah et al [ 65 ] with 21.9% in Ghana, and Mai et al [ 66 ] with 24.0% in Nigeria.…”
Section: Discussionmentioning
confidence: 93%
“…Another cross-sectional study in the Jimma Zone, Oromia Region, has reported an animal and herd level cattle prevalence of 16.4% and 4.3%, respectively [64]. Very recent studies have also recorded a prevalence of 11.9% and 22.5% in Afar National Regional State and East Wollega, Oromia Region, respectively [14,17].…”
Section: Seroprevalence Of Bovine Brucellosismentioning
confidence: 96%
“…Bovine brucellosis in Ethiopia is endemic and widely distributed in urban, peri-urban, highlands= and lowland areas with extensive and intensive farming, as well as smallholder farms and ranches in the country. It has caused high economic losses and is becoming a serious public health threat [14,46,47].…”
Section: Status Of Bovine Brucellosis In Ethiopiamentioning
confidence: 99%
See 2 more Smart Citations